Study on Ideological and Political Education of College Students in the New Era from the Perspective of “Circle Stratification” (Journal of Global Humanities and Social Sciences, 2025)
In the new era, “circle stratification” has transformed the paradigm of college students’ ideological and behavioral patterns, exhibiting characteristics of cognitive narrowing, social segregation, and ideological polarization, which presents a systematic challenge to conventional ideological and political education models. This phenomenon has introduced multiple challenges in communication mechanisms (symbol misalignment, channel barriers), educational subjects (cognitive intergenerational gaps, insufficient digital literacy), and educational evaluation (limited indicators, data latency). Utilizing university educational resources and practical scenarios, this study proposes an optimization framework of “communication optimization-subject empowerment-evaluation innovation”: at the communication level, achieving flexible integration of mainstream values and circle contexts through circle case embedding, lightweight content production, and scenario-based activity design; at the subject level, enhancing educators’  cross-circle guidance capabilities through teacher-student dialogue mechanisms and circle practice participation; at the evaluation level, implementing an evaluation system adapted to circle characteristics through differentiated indicator design and dynamic feedback mechanisms. This research extends the analytical scope of ideological and political education through the lens of “circle stratification” and offers strategic guidance for universities to overcome circle isolation and enhance the effectiveness of ideological and political education.